Hz. Peygamber (SAV)’in seyahat hayatı - Kartal, Fatma (My University, 2019)
Kur’ân-ı Kerîm’de pek çok âyette seyahat, yolculuk ve ulaşıma dair bilgiler verilmektedir. Yüce Allah Müslümanları yeryüzünü gezip görmeye teşvik etmişdir. Coğrafi şartlar gereği seyahat üzerine kurulu bir yaşamları olan Arap toplumunda özellikle ticaret seyahatleri yaygındı. Böyle bir ortamda doğup büyüyen Hz. Peygamber'in seyahat hayatını, seyahate dair uygulamalarını tespit ederek hazırladığımız araştırmamız, bizlere Kur’ân-ı Kerîm’i ve İslam’ı daha iyi anlamamızı sağlayacaktır. Hz. Peygamber’in seyahat hayatına dair topladığımız veriler Hz. Peygamber’in vefatından sonra İslam’ın dünyanın dört bir tarafına büyük bir hızla yayılışını anlamamıza ışık tutmaktadır. Ayrıca bu çalışma İslam’da ve Peygamberimiz’in hayatında seyahatin; ilim, ticaret, ziyaret, ibadet, cihâd gibi pek çok alanda uygulama olarak nasıl bir karşılığı olduğunu görmemizi sağlamıştır. Vahyin denetiminde Hz. Peygamber’in rehberliğinde seyahat esnasında oluşan ve bugün dahi dünyanın dört bir tarafında ortak uygulamalarla yaşanmaya devam eden bir seyahat kültürü vardır. Günümüzde dahi seyahate dair kullanılan ifadelerle Hz. Peygamber’le başlayan seyahat yaşantısının bağlantısını görmekteyiz. İşte bu bağlantının köklerine gidip daha iyi anlama ümidi ve amacı ile tezimizde Hz. Peygamber’in seyahatleri araştırılmıştır.

Many verses in the Holy Qur'an provide information on travel, travel, and transportation. Almighty Allah encourages Muslims to travel and explore the earth. Due to their geographical conditions, especially trade-driven journeys were common in the Arab communities whose lifestyle is based on traveling. Our study, which has been focused on determining the travel life and practices of the Prophet who was born and grown into such an environment, will enable us to better understand the Holy Quran and Islam. The information gathered and presented in this study about the traveling life of the Prophet Muhammad sheds light on our understanding of the rapid widespread of Islam in the world after the death of the prophet. Moreover, this study has enabled us to see how the travel in Islam and the life of our Prophet (pbuh) gets practiced as in many areas such as science, commerce, visitation, worship, and jihad. There is a travel culture that has been created during the journey of the Companions of the Prophet who has been living under the guidance of the Prophet and continues to live with common practices throughout the world even today. Even today, in some common expressions embedded in our daily language affiliated with the traveling, we see the connection of the travel life that started with the Prophet. With the hope of better understanding the roots of this connection, in this thesis, the travels of Prophet Muhammad have been investigated.
Keywords: Camel; Deve Sirah; Hz. Peygamber; Journey; Prophet Muhammad; Seyahat; Siyer; Transportation; Travel; Ulaşım; Yolculuk